Reorientasi Paradigma Pendidikan Keguruan: Telaah terhadap Rancangan Sertifikasi Kompetensi Pendidik dan Tenaga Kependidikan - Nur Ali Rahman (el Harakah: Jurnal Budaya Islam, 2005)
A good society can be seen by the positive characteristics displayed by its people. A person with positive characteristic is a product of a good quality of education. It is said that education quality is influenced by the quality of teachers. Low-qualified teachers are mostly related with the system of teacher development and the low-qualified institutions whose aim is to educate the future teachers. This article discusses the orientation of teacher education that has been programmed by government for several years. It is listed in 10 basic competences of professional teacher. The program of certification as the professional guarantee is also one of parts of this article. It can be assumed that to solve any kinds of educational problems, the renewal of orientation in developing education paradigm is highly needed. Masyarakat yang baik hanya dapat dibentuk dengan menampilkan individu-individu dengan karakter baik. Individu yang berkarakter baik dapat dibentuk melalui pendidikan yang berkualitas. Sedangkan, kualitas pendidikan banyak dipengaruhi oleh kualitas guru. Rendahnya kualitas guru banyak berkaitan dengan pola pengembangan guru dan banyaknya lembaga pendidikan berkualitas rendah yang menghasilkan guru. Artikel ini membahas orientasi pendidikan guru yang dicanangkan pemerintah beberapa tahun ini. Program-program tersebut tercakup dalam 10 kompetensi dasar untuk profesionalisme guru. Program sertifikasi sebagai penjamin juga menjadi salah satu bahasan di sini. Dapat disimpulkan bahwa untuk menyelesaikan masalah-masalah pendidikan, pembaharuan orientasi dalam pengembangan paradigma pendidikan sangat dibutuhkan.